A novel approach to formulate high flux multifunctional ultrafiltration membranes from photocatalytic titania composite precursors on multi-channel tubular substrates - Manjumol, K.; Sankar, S.; Nair, Balagopal; Midhun, M.; Mohamed, P.; Warrier, K. (Royal Society of Chemistry, 2016)
© 2016 The Royal Society of Chemistry.Anatase rich titanium dioxide ultrafiltration membranes with high filtration rates have been successfully developed on multi-channel tubular alumina substrates via aqueous sol-gel method from titania-alumina composite precursors containing 30 wt% alumina. The composite membrane material exhibited anatase phase stability above 800 °C and retained a BET surface area of 64 m2 g-1 even after calcination at 700 °C. Supported membranes on multi-channel substrates with an active layer thickness of 4 µm gave a water flux value of 215 L m-2 h-1 coupled with 80% rejection of Bovine Serum Albumin (BSA) with molecular weight 66 kD at 2 bar pressure. This is much higher compared to a flux of 27 L m-2 h-1 obtained for a single component titania membrane layer. The composite membrane materials showed excellent photocatalytic activity under UV irradiation such that a solution containing Methylene Blue (MB) dye showed 96% dye degradation within 2 h. Porous disc shaped substrates coated with the active titania composite layer showed methylene blue degradation of 44% under identical conditions. The present results point towards an excellent pathway for the development of multifunctional ultra-filtration membranes for water purification and also for other separation applications where separation together with photocatalysis will be of great importance.